PENGEMBANGAN MODUL IPA TERPADU BERBASIS KEARIFAN LOKAL PAPUA MATERI INTERAKSI MAHLUK HIDUP TERHADAP LINGKUNGAN - SRI LESTARI; TIURLINA SIREGAR; JONNER NAINGGOLAN (Program Magister Pendidikan IPA, Program Pascasarjana Universitas Cenderawasih, 2019)
Papua's local wisdom module is really needed to improve learning outcomes with contextual and tangible control where so far there has been lack of teaching materials based on local wisdom. This research is a research and development (Research & Development) that aims to find out how to develop integrated science modules based on local Papuan wisdom materials on the interaction of living things with the environment in class VII students of Nurul Huda Yapis Jayapura in knowing improvement in learning outcomes after using the module. The development model used is the ADDIE model (Analyze, Design, Development, Implementation, Evaluation) with an experimental design using a pre test post test one group design, which uses one research class with a sample of 37 students. The results showed. (1) The results of the feasibility test for the prepared learning modules, based on material validation, obtained an average of 90.6%, media validation with an average of 92%, educator responses 96.25% and mean responses of students by 90.7%. In general the average for the module feasibility test is 92.10% which means the module is very suitable for use in learning. (2) There is an increase in students' learning outcomes after using a module based on local Papuan wisdom, based on the n-Gain results in RPP 1 is 0.57, RPP 2 is 0.71 and RPP 3 is 0.75. The n-Gain average for the three RPPs is 0.68 with a moderate category which means the use of science modules based on local Papuan wisdom is quite effective in improving student learning outcomes.